Chapter Between Three Languages, Dialects and Forms of Mixed Speech: Dialect and Language Contacts in Ukrainian-Belarusian Transitional Area - DEL GAUDIO, Salvatore (Biblioteca di Studi Slavistici, 2018)
The territory roughly delimitated by the rivers Dnipro, Sož and Desna, geo-politically set between Ukraine, Belarus' and not far from the Russian Federation, presents a particularly interesting language situation. In this geo-dialectal "triangle" coexist and interact local dialects - also known as Ukrainian-Belarusian 'transitional' dialects - three standard languages (i.e. Ukrainian, Russian and Belarusian), and various forms of language mix. In this article we primarily intend to examine some fundamental issues related to dialectal contact and language distribution typical of this border area.